Gambaran Tingkat Stres Mahasiswa Fisioterapi ITSK RS dr. Soepraoen dalam Menyusun Skripsi - Provisa Redy Fernando; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:   the purpose of this study was to know an overview of stress level of Fisioterapi student in Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen  in working on thesis on the 2020/2021 academic years.Methods:   The research methodology used is quantitative with a descriptive approach to see a description of the level of stress that is being experienced by students when working on their thesis. The sample method in this research use the total sampling, with  the number  of  research  respondent  obtained  in  this  study  as  many  as 79 students in the 2021/2021 academic years.Results:   Most of the respondents (58.6%) were female and 44.3% of students were in their early adulthood. As many as 97% of students experienced mild stress and 3% experienced moderate stress. All students who experience moderate stress are female and are in early adulthood.Conclusion:   Most of the stress levels experienced by students working on theses are mild stress.